Simultaneous Catheter Replacement for Infectious and Mechanical Complications without Interruption of Peritoneal Dialysis. Issue 2 (March 2016) - Crabtree, John H.; Siddiqi, Rukhsana A.
Background: Conventional management for peritoneal dialysis (PD)-related infectious and mechanical complications that fails treatment includes catheter removal and hemodialysis (HD) via a central venous catheter with the end result that the majority of patients will not return to PD. Simultaneous catheter replacement (SCR) can retain patients on PD by avoiding the scenario of staged removal and reinsertion of catheters. The aim of this study was to evaluate a protocol for SCR without interruption of PD. Methods: Clinical outcomes were analyzed for 55 consecutive SCRs performed from 2002 through 2012 and followed through 2013. Results: Simultaneous catheter replacements were performed for 28 cases of relapsing peritonitis, 12 cases of tunnel infection, and 15 cases of mechanical catheter complications. All cases for peritonitis and tunnel infection and 80% for mechanical complications continued PD on the day of surgery using a low-volume, intermittent automated PD protocol. Systemic antibiotics were continued for 2 weeks postoperatively (up to 4 weeks for Pseudomonas ). Simultaneous catheter replacement was performed as an outpatient procedure in 89.1% of cases. Only 1 of 55 procedures was complicated by peritonitis within 8 weeks. No catheter losses occurred during this postoperative timeframe. Long-term, SCR enabled a median technique survival of 5.1 years. Conclusions: In most instances, SCR can be safely performed without interruption of PD for selected cases of peritonitis and tunnel infection and for mechanical catheter complications. The procedure spares the patient from a central venous catheter, a shift to HD, the psychological ordeal of a change in dialysis modality, and a second surgery to insert a new catheter.